ASPECTS REGARDING THE USE OF OXYTOCIN IN MARKETING - Mirela-Cristina VOICU; Elena-Mihaela ILIESCU (Challenges of the Knowledge Society)
The main purpose of the marketing activity is to convince consumers to purchase a good or service or to adopt a certain behavior. Companies make significant investments in this marketing activity aimed at persuading people to take action. We know on a scientific basis much of what lies behind consumer behavior. Mr. Kotler's black box is starting to become more and more transparent. Thus, current studies clearly support what marketers only suspected some time ago, namely that certain images or actions cause the human brain to release a series of hormones with different effects on the human body. Among these hormones, oxytocin stands out, called the happiness hormone or the love hormone due to its effect on people. Thus, through a marketing activity aimed at stimulating the release of this hormone in the human body, we can build trust in a product or brand, which will translate into a lasting relationship with consumers and, finally, into an effective marketing activity for the company. Being in a permanent search for those secrets that ensure the success of marketing campaigns, marketing specialists must also understand the perspective of human psychology and physiology involved in carrying out a convincing activity. In this context, the following paper reveals important aspects regarding the necessity of understanding how oxytocin is influencing consumer behavior together with ways in which this hormone can be stimulated for the use of the company’s marketing activity.